More and more of less and less: Is genomics-based breeding of dry direct-seeded rice (DDSR) varieties the need of hour? - Sagare, Deepti B.; Abbai, Ragavendran; Jain, Abhinav; Jayadevappa, Pranesh K.; Dixit, Shilpi; Singh, Arun Kumar; Venkateshwarlu, Challa; Alam, Shamshad; Singh, Uma Maheshwar; Yadav, Shailesh; Sandhu, Nitika; Kabade, Pramod G.; et al. (Wiley, 2020)
Rice is a staple food for half of the world's population. Changing climatic conditions, water and labour scarcity are the major challenges that shall limit future rice production. Dry direct‐seeded rice (DDSR) is emerging as an efficient, resources conserving, mechanized, climate smart and economically viable strategy to be adopted as an alternative to puddled transplanted rice (TPR) with the potential to address the problem of labour‐water shortages and ensure sustainable rice cultivation. Despite these benefits, several constraints obstruct the adoption of DDSR. In principle, the plant type for DDSR should be different from one for TPR, which could be achieved by developing rice varieties that combine the traits of upland and lowland varieties. In this context, recent advances in precise phenotyping and NGS‐based trait mapping led to identification of promising donors and QTLs/genes for DDSR favourable traits to be employed in genomic breeding. This review discusses the important traits influencing DDSR, research studies to clarify the need for breeding DDSR‐specific varieties to achieve enhanced grain yield, climate resilience and nutrition demand. We anticipate that in the coming years, genomic breeding for developing DDSR‐specific varieties would be a regular practice and might be further strengthened by combining superior haplotypes regulating important DDSR traits by haplotype‐based breeding.